2005
DOI: 10.1080/00071660500098210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of collection frequency on quantitative and qualitative characteristics of pigeon (Columba livia) semen

Abstract: The aim was to estimate the optimal frequency of semen collection from pigeons in relation to ejaculate volume, sperm concentration, total spermatozoa in ejaculate and percentage of live morphologically normal cells. The study was carried out on 455 ejaculates collected from two groups of pigeons, each of 10 males (group I: meat-type breed; group II: fancy pigeon). The birds were selected and kept individually in cages under a natural photoperiod. A two-person technique was used for semen collection (lumbo-sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Although criticism of some of the above classification systems has been expressed, each relies on the identification of specific sperm abnormalities and each presents a detailed list of observable anomalies, most of which have been thoroughly described by light microscopy supported by numerous ultrastructural studies. In contrast, the morphological classification of avian sperm abnormalities lacks uniformity and although the presence of abnormal sperm has been reported in a variety of bird species [17,21,26,27,28,35,41,57], the anomalies are described in broad and variable terms which makes it difficult to draw meaningful comparisons. The lack of detailed descriptions of avian sperm abnormalities is compounded, with few exceptions [19,22,29,30,31], by a dearth of supportive ultrastructural data.…”
Section: Cytoplasmic Dropletsmentioning
confidence: 99%
“…Although criticism of some of the above classification systems has been expressed, each relies on the identification of specific sperm abnormalities and each presents a detailed list of observable anomalies, most of which have been thoroughly described by light microscopy supported by numerous ultrastructural studies. In contrast, the morphological classification of avian sperm abnormalities lacks uniformity and although the presence of abnormal sperm has been reported in a variety of bird species [17,21,26,27,28,35,41,57], the anomalies are described in broad and variable terms which makes it difficult to draw meaningful comparisons. The lack of detailed descriptions of avian sperm abnormalities is compounded, with few exceptions [19,22,29,30,31], by a dearth of supportive ultrastructural data.…”
Section: Cytoplasmic Dropletsmentioning
confidence: 99%
“…In the Houbara bustard macrocephalic sperm are 14 reported to occasionally be associated with multiple tails [40]. Although macrocephalic sperm have been reported in other avian species [6,32,[47][48][49], no mention is made of multiple tails or other defects associated with this anomaly. A more careful assessment of avian sperm defects may clarify this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Ferdinand (1992) described a wide range of acrosome defects in the goose and Klimowicz et al (2005), without providing any detail, mentioned the presence of acrosome defects in the pigeon. Maeda et al (1986) reported swollen acrosomes in chickens, although this only occurred after the cells had been treated with cryo-protectants.…”
Section: Head Defectsmentioning
confidence: 99%
“…Midpiece abnormalities appear to be a common defect of avian species, particularly defects described as "bent midpiece" and "deformed midpiece" (Chelmońska et al, 2008;Klimowicz et al,. 2005;Maeda et al, 1984;Nwakalor et al, 1988;Penfold et al, 2000;Siudzińska and Łukaszewicz, 2008;Umapathy et al, 2005).…”
Section: Tail Defectsmentioning
confidence: 99%
See 1 more Smart Citation